Measurements of a 5 : 1 blood pump model - Ong, Wendy (2015)
This report represents the measurements of the velocity of the fluid flow between the clearance gap between the front volute case and the impeller of the 5:1 enlarged model of the Kyoto University Magnetically Suspended Centrifugal Blood Pump. This blood pump has a magnetically suspended impeller to eliminate the use of shafts, bearings and seals, thus eliminates the conventional problems of heat generation in a blood pump and leakages around the seal interface. An enlarged model was built so that the fluid flow in the gap could be measured. Hot and cold wire anemometries were used in this experiment to measure the flow velocity. Three different probes with protrusion depths of 0.25 mm, 0.50 mm and 0.75 mm were used to measure seven different radial position from the eye of the impeller, namely 69.5 mm, 78 mm, 86.5 mm, 95 mm, 103.5 mm, 112 mm and 120.5 mm. For each position, seventy two readings were taken, at an angular position increment of 5° intervals, from 0° to 360°. The results showed that there is an obvious washout effect in the region around the splitter plate of the double volute, around 160° to 200° as it flows more in the radial direction towards the eye. This is important as to prevent blood cells from accumulating in the clearance gap which leads to higher chances of shear due to the impeller operation, resulting in thrombus formation and blood clot aggregation.